Evaluasi Kinerja Perusahaan Daerah Air Minum (PDAM) Lombok Timur Berbasis ISO 9001:2015 - Murnan Murnan; Kiki Yulianto; Umar Umar (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2022)
The research aimed at determining the fulfillment of the Quality Management System (QMS) standard atPDAM Lombok Timur based on ISO 9001:2015. The research wasconducted as field research by collecting information or data directly about the existing facts in the field relating to research problems. Related data to QMSimplementation based on the ISO 9001:2015 standard was collected using a document checklist system and supported by interviews and observations of informants followed by triangulation. The research used qualitative approach analysing. Application of Gap Analysis in Evaluating the Implementation of the ISO 9001:2015 Standard lead to the finding that PDAM Lombok Timur has not utilized ISO 9001:2015 as a QMS standard but several clauses in ISO 9001:2015 have been implemented. The clauses that need to be maintained are Scope, Development, Performance Evaluation and Organizational Context. While the Clauses of Terms and Definitions, Leadership, Operations and Planning are still to be developed. Meanwhile, the Normative Reference clauses and Support should be provided and improved. PDAM Lombok Timur may develop a QMS that refers to ISO 9001:2015, obtaining ISO guidance, develop a corporate learning culture and collaborate on GCG and ISO systems according to SMM company standards for advanced